The Successful Practice of Chinese-Chinese Female Legislators in Post-New Order Indonesia - Widjaya, Adeline Ilissa; Perdana, Phil. Aditya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
May 1998. According to Walujono, Suharto's rule, which led to the economic crisis in Indonesia during the New Order era, led the public to scapegoat ethnic Chinese as the perpetrators of the crisis.Their shops were robbed, looted, burned, and many ethnic Chinese women were raped and murdered.The representation of victims' identities in the media emphasized the characteristics of young, non-Muslim, non-indigenous, Chinese, and wealthy women.Hikmawati added that the rape was aimed at destroying the "woman"'s community of origin because women were viewed as symbols of a group's honor.Women's sexuality was considered not their own property and authority, but rather the property of their community, namely their father or husband.The research method used is qualitative, in which the researcher will attempt to describe and illustrate the data and information obtained related to the problem being studied.According to Creswell, qualitative research is an approach that explores and understands the intentions of an individual or group regarding a particular social phenomenon or problem.This approach was chosen because it allows for exploration of a specific phenomenon, specifically the success of ethnic Chinese female legislators in Indonesia after the New Order.In the case of the success of ethnic Chinese female legislators in Indonesia during the New Order, similarities and differences were found in the campaign strategies and success factors of Theresia Megawati Wijaya during her first term as a member of the Tangerang City DPRD compared to Me Hoa's three-term tenure as a member of the Central Bangka DPRD.Initially, both Theresia Megawati Wijaya and Me Hoa, as ethnic Chinese women, were equally successful due to their strong social, cultural, and symbolic capital, compared to their economic capital.